New forces at work in refining : industry views of critical business and operations trends - Peterson, D. J.; Mahnovski, Sergej; Science and Technology Policy Institute (Rand Corporation); Rand Corporation; National Energy Technology Laboratory (U.S.) (Santa Monica, CA : RAND, 2003)
Reports the results of discussions with representatives of refining firms, technologies and services providers, research institutions, and other organizations on current and future trends in the U.S. refining industry. Discussants were generally optimistic about the future of the industry but were concerned about the effects of environmental regulations. They recommended that the Department of Energy assume a more prominent policy role on refining and fuels issues.
Introduction: A Critical Infrastructure -- The Refining Industry and Petroleum Products Markets -- Refinery Operations and Technologies -- Regulatory and Financial Environment -- The Refining Industry in a New Era: Key Findings and Policy Issues.
"Science and Technology."
Includes bibliographical references (p. 113-115).
Also available on the internet via WWW in PDF format.
Keywords: Petroleum industry and trade -- Technological innovations -- United States; Petroleum -- Refining -- United States; Technological forecasting -- United States; Technology and state -- United States; Technology assessment -- United States